Detox Fashion Case Studies (Textile Science and Clothing Technology,, 2018)
This fourth volume on detox fashion focuses on case studies, which are essential to showcase how practical applications have been accomplished, and provide an opportunity for others to (learn about and) adopt the best practices, challenges and practical implications. The book consists of three core chapters: Detoxifying the Supply Chain: Slow Production Networks in South-East European Garment Factories; Detoxifying the Luxury and Fashion Industry: The Case of Market-driving Brands; and Detox My Fashion under Mission 2020-Case Studies from Different Brands.